Effect of Plant Growth Regulators (PGRs) on Biomass and Flavonoid Production of Talinum paniculatum Callus Culture - Sarah Mega Pratenna Kaban; Ratih Restiani; Dwi Aditiyarini (Jurnal Biodjati, 2024)
Talinum paniculatum Jacq (Gaertn), locally known as Javanese Ginseng, is an essential medicinal plant characterized by high flavonoid content with antioxidant and antimicrobial activities. Compared to other natural sources, a larger number of T. paniculatum leaves is required to obtain high amounts of flavonoid for drug development. In this context, in vitro culture can be used to increase flavonoid production in a controlled condition without reducing plant population. The concentration of Plant Growth Regulators (PGRs) is capable of influencing biomass and flavonoid accumulation in callus culture from several species. Despite these benefits, there is limited information about the optimal concentration of PGRs for flavonoid production from T. paniculatum callus culture. Therefore, this study aimed to investigate the optimum concentration of 2,4-D and kinetin for callus growth, as well as flavonoid production from T. paniculatum. The investigation was carried out using a completely randomized design (CRD), where young leaves explants were cultured on MS media supplemented with various concentrations of 2,4-D (0, 0.5, 1, 2) mg/L and kinetin (0, 0.5, 1, 2) mg/L for callus and flavonoid production. The results showed that the highest callus biomass of 0.105 g was produced from MS medium with 2 mg/L of 2,4-D and 1 mg/L of kinetin. Meanwhile, the highest total flavonoid content of 25.66 mg QE/g DW was produced from media supplemented with 1 mg/Lof 2,4-D and 2 mg/L of kinetin. These results showed that different combinations of 2,4-D and kinetin were required to increase biomass and flavonoid production. In conclusion, this study provided valuable information for the development of bioactive compounds through in vitro culture.